Analisis Kemampuan Pengelolaan Keuangan dan Gaya Hidup terhadap Prestasi Belajar Mahasiswa Penerima Kip-Kuliah - Manoma, Suharli (Balance : Jurnal Akuntansi dan Manajemen, 2025)
This study aims to analyze and obtain empirical evidence regarding the ability to manage finances and lifestyle and their impact on the academic achievement of KIP-Kuliah recipient students at Hein Namotemo University. The type of research used is quantitative research with a descriptive approach. This study uses primary data by distributing questionnaires to respondents. The sampling technique is using Non-Probability Sampling with Convenience Sampling technique. The number of samples used is 30 respondents. The analysis used in the study is a multiple linear regression analysis model. Based on the results of the data analysis, it is known that the variables of financial management ability and lifestyle statistically have a positive and significant effect on the academic achievement of KIP-Kuliah recipient students. While the results of the simultaneous test show that the variables of financial management knowledge and lifestyle together have a significant effect on the academic achievement of KIP-Kuliah recipient students at Hein Namotemo University. The results of the determinant coefficient (R2) obtained an R-square value of 0.423 or 42.3%. This shows that 42.3% of the learning achievement of students receiving Kip-Kuliah is influenced by factors such as financial management skills and lifestyle, while the remaining 57.7% (100% - 42.3%) is influenced by other factors not explained in this study.